Analisis Faktor Risiko Infeksi Saluran Pernapasan Akut pada Anak Balita di Wilayah Kerja Puskemas Harapan Raya Kota Pekanbaru - Annisa Salsabila; Zahtamal Zahtamal (Pelantar Press, 2023)
ARI is a type of infectious disease that occurs in the respiratory tract. ARI often occurs in toddlers even be the cause of toddlers mortality today. The purpose of this study was to know the correlation of birth weight, nutritional status, exclusive breastfeeding, immunization status, exposure to cigarette smoke and residencial density by ARI incidence. This research method using analytic survey with cross sectional approach in Harapan Raya Health Center. The population of all toddlers in Harapan Raya Health Center ( 6553) , the number ofÂ samples are 66. The instrument used was a questionnaire; maternal and child health book. Analysis using chi square test with significance level ( Î± = 0.05 ). The result of the research can be conclude that the relationship between birth weight (p-value = 0,000; PR = 3,56), nutritional status (p-value = 0,000; PR = 3,7), exclusive breastfeeding (p-value = 0,000; PR = 12,67), immunization status (p-value = 0,000; PR = 2,7), exposure to cigarette smoke (p-value = 0,000; PR = 0,109)Â and residencial density (p value = 0,000; PR = 2,15) with events of ARI in toddlers at Harapan Raya Health Center. Based on the research results, it is known that of all the variables studied, exclusive breastfeeding is the biggest risk factor causing the incidence of ARI in toddlers in the working area of the Harapan Raya Community Health Center, Pekanbaru City. It is hoped that parents will maintain a healthy environment, provide nutritious food, be active in immunization, provide exclusive breastfeeding, and if there is a family member who smokes, try to not smoke around toddlers.Â